PARAGRAPH WRITING WITH SENTENCE CARDS MEDIA ON INDONESIAN LANGUAGE LEARNING OF SIXTH GRADE STUDENTS - M. G. Rini Kristiantari; I Gusti Agung Oka Negara (Jurnal Pendidikan dan Pengajaran, 2017)
This research was aimed at improving paragraph writing ability of the sixth-grade students of SDN 19 Pemecutan Denpasar Bali by sentence cards media. The approach used in this research is qualitative research with action research method. The research data was students’ paragraph writing, document study in the form of the result of students’ writing, observation, and interview. The research data in the form of students’ paragraphs, students’ active participation, was collected through the paragraph composition test, document study in the form of students’ paragraph writing, observation, and interview. The data was taken from the teacher and 50 students of sixth grade SD Negeri 19 Pemecutan Denpasar Bali. The collected data was described qualitatively. The result showed improvement both from the result and student’s active participation in students’ paragraph learning. This was shown by the mean score of pre-test to post-test which was improved from 65.7 to 83.92. this was also shown by the students’ active participation which was positively changed from 36% to 77.33%. This result showed that the use of sentence cards media in writing learning can improve student’s ability in paragraph writing.